Integrated delivery systems: has their time come in Canada? - Leatt, P (1996)
In the 1990s every Canadian province is struggling to reduce health care expenditures without jeopardizing access to health care or quality of care. The authors propose a new model for health care delivery: the Canadian Integrated Delivery System (CIDS). A CIDS is a network of health care organizations; it would provide, or arrange to provide, a coordinated continuum of services to a defined population and would be held clinically and fiscally accountable for the outcomes in and health status of that population. A CIDS would serve 100,000 to 2 million people; the care it would provide would be funded on a capitation basis. For providers, there would be explicit financial incentives to minimize costs. At the same time, service quality and consumer choice of primary care practitioner would be maintained. Primary care physicians and specialists would work with other health care service providers to offer a full spectrum of care. CIDS providers would form strategic alliances with community agencies, hospitals, the private sector and other health care services not managed by the CIDS, as needed. For physicians, affiliation with a CIDS that provided strong clinical leadership could be beneficial to their income stability and autonomy. Pilot projects of this model in several communities would determine whether this concept is feasible in the Canadian health care context.